2016
DOI: 10.1186/s11671-016-1333-9
|View full text |Cite
|
Sign up to set email alerts
|

Broadband Metallic Planar Microlenses in an Array: the Focusing Coupling Effect

Abstract: The microlens arrays (MLAs) are widely utilized for various applications. However, when the lens size and the spacing between two adjacent microlenses are of the length scale of the working wavelength, the diffraction effect plays a vital role in the final focusing performance. We suggest a kind of broadband metallic planar microlenses, based on which the ultra-compact microlens arrays are also constructed. The focusing coupling effect revealing for such devices is then investigated in detail by using the fini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Besides, the peak intensity values are uniformly distributed at the array plane, which is a great aspect of these metalens arrays. On the other hand, remarkably, no significant fringing effect exists on the achieved focal spots, which is another superior characteristic of this study comparing to the results of previously reported metallic planar microlens arrays [48], which clearly suffer from plasmonic coupling effects. This also simplifies the accurate control over the focusing performance of metalenses in an array.…”
Section: The Effect Of the Metalens Array Sizesupporting
confidence: 55%
“…Besides, the peak intensity values are uniformly distributed at the array plane, which is a great aspect of these metalens arrays. On the other hand, remarkably, no significant fringing effect exists on the achieved focal spots, which is another superior characteristic of this study comparing to the results of previously reported metallic planar microlens arrays [48], which clearly suffer from plasmonic coupling effects. This also simplifies the accurate control over the focusing performance of metalenses in an array.…”
Section: The Effect Of the Metalens Array Sizesupporting
confidence: 55%
“…The focal spots under the white light illumination have the similar lateral dimensions as those under a single wavelength, while the broadband focal length is approximately the average of the focal lengths at the SP-enhanced wavelengths. In addition, the focusing coupling effect in microlens array which we had analyzed in our previous research [37] emerges in the obtained focusing patterns as the regions C, D, and E flagged in Fig. 8 (b1) and (b2).
Fig.
…”
Section: Resultsmentioning
confidence: 82%
“…The reported plasmonic lenses are based on slits [17,18], and less attention has been dedicated to the utilization of hole array. Few broadband spectrum lenses for the visible range based on nanohole array have recently been proposed [19][20][21], but they suffer from low transmittance, polarization sensitivity, and large size. In the meantime, plasmonics tapers by using grating-coupled SPPs made nanofocusing feasible [22,23].…”
Section: Introductionmentioning
confidence: 99%